Building peer social support as a mental disorder solution for the blind - Habibah, Umi; Sucipto, Ade (Journal of Advanced Guidance and Counseling, 2020)
Blind people are people with disabilities due to the dysfunction of the sense of vision, this condition triggers the birth of various mental disorders. This qualitative study tries to examine the mental problems of blind vision disorders in the Sahabat Mata Semarang Community and the solutions the management is trying to overcome. The results of the study show that mental disorders with visual impairments include difficulties in adapting to the environment, anxiety about the future of a career and soul mate, prolonged stress due to dependence on others and no economic independence, and do not yet have self-acceptance. One of the efforts undertaken by the management of this community is to build peer social support, namely support provided by fellow blind people in the form of emotional support, appreciation support, structural support, information support, and real assistance. The various supports are built by holding regular recitals, monthly community meetings, and building good interpersonal relationships. Such peer social support, felt blind can provide alternative solutions and a variety of mental disorder problems they experience.